Bureaucracy and professionalism in an educational organisation : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Education at Massey University - Shaw, Brian (Massey University, 1971)
The development of human societies has been in essence a development of forms of social organisation. In modern societies, social organisation is complex, diverse, and characterised by conditions of industrialisation, division of labour, urbanisation, and the aggregation of individuals into large organisations with specific purposes. One form of social organisation which has developed to maintain social relationships in such conditions is the bureaucracy. Bureaucracies as structures, or systems of rational procedures deliberately set up to achieve specifically prescribed social ends, affect to some degree the lives of all citizens of modern societies. Educational organisations are bureaucratised to varying degrees, and the rapid and accelerating demand for popular education suggests that bureaucratisation is likely to be a dominating characteristic of education in the future.
Keywords: School personnel management; Teaching -- Professional ethics; Bureaucracy; Professional ethics